Deposition of TiN-based coatings using vacuum arc plasma in increased negative substrate bias voltage - Kuprin, A.S.; Leonov, S.A.; Ovcharenko, V.D.; Reshetnyak, E.N.; Belous, V.A.; Vasilenko, R.L.; Tolmachova, G.N.; Kovalenko, V.I.; Klimenko, I.O. (Вопросы атомной науки и техники, 2019)
The paper presents the results of the study on the influence of a high substrate bias voltage from 300 up to 1300 V on the titanium nitride coating deposition under nitrogen pressure of 2 Pa. The deposition rate, phase and chemical composition, adhesion and mechanical properties of coatings, macroparticle number and size distribution were investigated.